Mekanisme Pertahanan Ego Tokoh Utama Pria dalam Novel Randha Sulasih Karya Tulus Setiyadi (Kajian Psikoanalisis Sigmund Freud) - Mega Yuli, Agnes Meilani; Darni, Darni (Jurnal Online Baradha, 2023)
Abstract The misalignment of id, ego, and superego as the structure of human personality can cause personality dynamics in the form of anxiety. Like the main male character in the novel Randha Sulasih by Tulus Setiyadi, this anxiety will be overcome by ego defense mechanisms. To find out the ego defense mechanism used by the character, it will be analyzed with Sigmund Freud's Psychoanalysis study. This research uses qualitative descriptive method. The data source is Randha Sulasih novel by Tulus Setiyadi. The data in this study are in the form of words, sentences and paragraphs about the atmosphere and events in the story of this novel. The techniques used in this research are reading and recording techniques. The data is then grouped based on the data table that has been provided, then analyzed systematically using qualitative descriptive methods concisely and clearly. The result of this research is the personality structure owned by Saikun's character which is most prominent is the ego defense mechanism used by the male main character in this novel, which is five, namely repression, diversion, rationalization, denial, and sublimation. The most common defense mechanism is diversion. The causes of ego defense mechanisms carried out by Saikun are divided into three, namely anxiety from outside, anxiety from within, and anxiety due to superego violence. Keywords: repression, distraction, rationalization, denial Abstrak Adanya ketidak selarasan id, ego, dan superego sebagai struktur kepribadian manusia dapat menimbulkan dinamika kepribadian berupa kecemasan. Seperti tokoh utama pria dalam novel Randha Sulasih karya Tulus Setiyadi yang kecemasan ini akan diatasi dengan mekanisme pertahanan ego. Untuk mengetahui mekanisme pertahanan ego yang digunakan oleh tokoh maka akan dianalisis dengan kajian Psikoanalisis Sigmund Freud. Penelitian ini menggunakan metode deskriptif kualitatif. Sumber data novel Randha Sulasih karya Tulus Setiyadi. Data dalam penelitian ini berupa kata, kalimat maupun paragraf mengenai suasana dan kejadian dalam cerita novel ini. Teknik yang digunakan dalam penelitian ini adalah teknik baca dan catat. Data kemudian dikelompokkan berdasarkan tabel data yang sudah disediakan, kemudian dianalisis dengan sistematis menggunakan metode deskriptif kualitatif dengan ringkas dan jelas. Hasil penelitian ini adalah struktur kepribadian yang dimiliki tokoh Saikun yang paling menonjol adalah mekanisme pertahanan ego yang digunakan tokoh utama pria dalam novel ini berjumlah lima yaitu represi, pengalihan, rasionalisasi, denial, dan sublimasi. Mekanisme pertahanan yang paling sering dilakukan adalah pengalihan. Penyebab mekanisme pertahanan ego dilakukan oleh tokoh Saikun dibagi menjadi tiga yaitu Kecemasan dari luar, kecemasan dari dalam, dan kecemasan karena kekerasan superego. Kata kunci : represi, pengalihan, rasionalisasi, denial